2018
DOI: 10.1080/0142159x.2018.1484897
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating expertise: Perceptual and adaptive learning technology in medical learning

Abstract: Through relatively short training interventions, PALMs produce large and durable improvements in trainees' abilities to accurately and fluently interpret clinical signs and tests, helping to bridge the gap between novice and expert clinicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 31 publications
0
62
0
2
Order By: Relevance
“…Learners practice using real-world images and performance is measured throughout -rather than at the end of -the learning process to provide feedback in realtime. 21 While trainees are generally able to follow and easily recognize patterns highlighted in a presentation, they classically encounter di culty when a new image is encountered independently. 23 Hence, the development of expertise requires a re ned "information extraction system, not a storehouse of memorized instances."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learners practice using real-world images and performance is measured throughout -rather than at the end of -the learning process to provide feedback in realtime. 21 While trainees are generally able to follow and easily recognize patterns highlighted in a presentation, they classically encounter di culty when a new image is encountered independently. 23 Hence, the development of expertise requires a re ned "information extraction system, not a storehouse of memorized instances."…”
Section: Discussionmentioning
confidence: 99%
“…20 Feedback provided after each classi cation task further strengthens learning. PALMs have been employed for improving expertise in several areas of medical teaching, 21 including dermatology, 22 histopathology, 23 transesophageal echocardiography (TEE), 24 and electrocardiography (ECG). 25 We developed a PALM for teaching the discrimination of ve common optic nerve ndings (glaucomatous changes, swelling, pallor, myopia, and normal nerve) and examined its effectiveness, compared to a video didactic lecture, in promoting optic nerve diagnostic skills among medical students in a prospective randomized trial.…”
Section: Introductionmentioning
confidence: 99%
“…Visual expertise requires individuals to enact different types of processes. The perceptual processes underlying visual expertise are fundamental because professionals cannot only rely on procedural and declarative knowledge (Kellman & Krasne, 2018) to perform their tasks. These processes can be divided into the following four stages: 1) identification of things that are worthy of further analysis, 2) recognition of relevant sections of images, 3) identification of target sections (e.g., lesions) and 4) diagnosis (Waite et al, 2019).…”
Section: Visual Expertise Skills In Dermatological Areasmentioning
confidence: 99%
“… 10 As a result, adaptive learning can optimise learning efficiency. 11 A recent systematic review and meta-analysis demonstrated that AEEs appear to be effective in improving skills in both professionals and students. 9 Adaptive learning can be accurate and fluent and helps guide the spacing and sequence of learning events.…”
Section: Introductionmentioning
confidence: 99%